Economy ; Packaging the president ; Katy! - Lazaro, Cheche; Dela Cruz, Katy (Probe Productions, 1988)
Looks at the economic strategy of the Philippines government. Focuses on the propaganda battle in the U. S. presidential elections of 1988. The Legendary Mommy Katy dela Cruz is the subject of a Filipino musicale about her life and as a vaudeville star.